Emerging oxidized and defective phases in low-dimensional CrCl3. Issue 16 (14th July 2021) - Mastrippolito, Dario; Ottaviano, Luca; Wang, Jing; Yang, Jinjin; Gao, Faming; Ali, Mushtaq; D'Olimpio, Gianluca; Politano, Antonio; Palleschi, Stefano; Kazim, Shafaq; Gunnella, Roberto; Di Cicco, Andrea; et al.
Abstract : Emerging defect- and oxidation-induced extrinsic phases are discovered in low-dimensional CrCl3 . Abstract : Two-dimensional (2D) magnets such as chromium trihalides CrX3 (X = I, Br, Cl) represent a frontier for spintronics applications and, in particular, CrCl3 has attracted research interest due its relative stability under ambient conditions without rapid degradation, as opposed to CrI3 . Herein, mechanically exfoliated CrCl3 flakes are characterized at the atomic scale and the electronic structures of pristine, oxidized, and defective monolayer CrCl3 phases are investigated employing density functional theory (DFT) calculations, scanning tunneling spectroscopy (STS), core level X-ray photoemission spectroscopy (XPS), and valence band XPS and ultraviolet photoemission spectroscopy (UPS). As revealed by atomically resolved transmission electron microscopy (TEM) and energy dispersive X-ray (EDX) analysis, the CrCl3 flakes show spontaneous surface oxidation upon air exposure with an extrinsic long-range ordered oxidized O–CrCl3 structure and amorphous chromium oxide formation on the edges of the flakes. XPS proves that CrCl3 is thermally stable up to 200 °C having intrinsically Cl vacancy-defects whose concentration is tunable via thermal annealing up to 400 °C. DFT calculations, supported by experimental valence band analysis, indicate that pure monolayer (ML) CrCl3 is an insulator with a band gap of 2.6 eV, while the electronic structures of oxidized and Cl defective phases of ML CrCl3, extrinsically emerging in exfoliated CrCl3 flakes, show in-gap spin-polarized states and relevant modifications of the electronic band structures.